Synthetic varieties of winter rye (Secale cerecale L.) - В. В. Скорик; Волод. В. Скорик; Н. В. Симоненко; О. П. Скорик (Plant Varieties Studying and Protection)
Possibility of heterosis effect approbation by using synthetic varieties of winter rye was discussed. Heterosis level of first five generation of rye synthetics did not decrease. Considerable yield decrease of winter rye grain took place in later generations. Concept of synthetic varieties of winter wheat creation in Ukraine is prospective, though it requires scientific, economical and legal improvement.